68.1k views
0 votes
Find all the possible of x for which of the below is true:


(2x)/(x + 3) + (3)/(x - 3) = (8)/(x^(2) - 9 )


User Justin Li
by
4.9k points

1 Answer

2 votes

Answer:

x =
(1)/(2) , x = 1

Explanation:

Given


(2x)/(x+3) +
(3)/(x-3) =
(8)/(x^2-9) ← denominator is a difference of squares


(2x)/(x+3) +
(3)/(x-3) =
(8)/((x+3)(x-3))

Multiply through by (x + 3)(x - 3) to clear the fractions

2x(x - 3) + 3(x + 3) = 8 ← distribute left side and simplify

2x² - 6x + 3x + 9 = 8

2x² - 3x + 9 = 8 ( subtract 8 from both sides )

2x² - 3x + 1 = 0 ← in standard form

(2x - 1)(x - 1) = 0 ← in factored form

Equate each factor to zero and solve for x

2x - 1 = 0 ⇒ 2x = 1 ⇒ x =
(1)/(2)

x - 1 = 0 ⇒ x = 1

User Grant Thomas
by
5.0k points